Analysis on Pre-Service Teacher’s Questioning Skills During Class Interaction - Melawati, Randi; Arini, Restu (Jurnal Ilmiah Wahana Pendidikan, 2023)
Questioning skill is one of the most common techniques for maintaining class interaction as well as stimulating students' thinking and guiding the development of knowledge that promotes a successful learning process. This study examines the questions delivere by Pre-service Teachers based on cognitive skills based on Bloom's Taxonomy. This study uses descriptive qualitative research in which the data were analyzed using content analysis. The data are taken from videos of the performances of Pre-Service teachers’ of the English Education department who were practicing Microteaching. The results found 20 questions of Low Order Thinking Skills (LOTS) and seven questions of High Order Thinking Skills (HOTS) questions used by the PST. The LOTS consists of 5 questions of C1 (Remembering), 11 questions of C2 (Understanding), 2 questions of C3 (Applying); while the HOTS questions includes four questions of C4 (Analyzing), one question of C5 (Evaluating), and one question C6 (Creating) out of a total of 26 questions. This findings indicates the use of HOTS based questions in class is less than LOTS which means that the pre-service teachers’ skills in making HOTS based questions need to be improved.